Problems of Islamic Education in the Reality of Muslim Society - Andi Jufri; Sabran Kamal; Andi Anderus (Yayasan Rahmat Islamiyah, 2026)
This study investigates the complex structural, philosophical, and operational challenges confronting Islamic education within the contemporary reality of Muslim societies. Utilizing a qualitative research methodology based on literature review and content analysis, this paper systematically categorizes these core problems into three primary dimensions: the epistemological dichotomy between religious and secular knowledge, curricular stagnation lacking technological and critical-thinking integration, and institutional limitations regarding infrastructure, funding, and teacher professionalism. The findings indicate that these challenges stem from historical post-colonial legacies, socio-economic disparities, and rigid traditionalism in pedagogical practices. To overcome these crises, the paper argues for a strategic shift toward integrated education (integrasi-interkoneksi), pedagogical modernization, and policy reforms that harmonize Islamic ethical values with contemporary scientific demands, thereby repositioning Islamic education as an effective engine of societal transformation.